1989
DOI: 10.1159/000243104
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Psychological Stress, Dermatoglyphic Asymmetry and Pregnancy Outcome in the Pigtailed Macaque (<i>Macaca nemestrina</i>)

Abstract: The relationships between maternal psychosocial stress during pregnancy and asymmetry in dermal ridge count, gestation length, birth weight percentile and survival were examined in 68 pigtailed macaque offspring. Twenty-five pregnant females were stressed daily by capture from 30 through 130 days postconception; 43 control unstressed females were housed under conditions of minimal disturbance. The difference between total intercore dermal ridge counts between right and left hands of the offspring was used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 45 publications
2
31
1
1
Order By: Relevance
“…In non-human primates, dental and dermatoglyphic asymmetries have been shown to increase with prenatal maternal stress in pigtailed (Newell-Morris, Fahrenbruch, & Sackett, 1989) and rhesus macaques (Kohn & Bennet, 1986); but this proposition is not without criticism (e.g. see Saunders & Mayhall, 1982).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In non-human primates, dental and dermatoglyphic asymmetries have been shown to increase with prenatal maternal stress in pigtailed (Newell-Morris, Fahrenbruch, & Sackett, 1989) and rhesus macaques (Kohn & Bennet, 1986); but this proposition is not without criticism (e.g. see Saunders & Mayhall, 1982).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Dans une étude sur le stress prénatal maternel lors d'un désastre, Mednick a démontré que l'exposition prénatale au tremblement de terre qui s'est produit en Chine en 1976 (qui a tué plus de 240,000 personnes) est associée à un thalamus et à un noyau caudé significativement plus petits, et à des ventricules plus grands à l'âge de 18 ans que ceux d'une cohorte d'enfants nés un an plus tard (Mednick, 1998, communication personnelle). Des résultats similaires ont été obtenus dans des études contrô-lées chez des animaux (Newell-Morris et al, 1989 ;Schneider et al, 1992 ;Schneider et Cole, 1993).…”
Section: Les Effets Du Stress Prénatal Maternelunclassified
“…It is interesting to note that Barker's group [24] reports fingerprint abnormalities in all these affected adults, which appear to be a marker of an anomaly or stress that occurred during intrauterine life, as in the findings of Newell-Morris et al [13].…”
Section: Environmental Stressmentioning
confidence: 74%
“…Two publications give representative accounts of this phenomenon. That of Newell-Morris et al [13] reported that in the macaque monkey, following maternal psychosocial stress, the newborns had dermatoglyphic asymmetry between the right and left hands that was significantly greater than in the control group. This maternal stress did not lead to any significant differences in the duration of pregnancy, birth weight or mean survival.…”
Section: Reliermentioning
confidence: 90%